Thermal Scalar Field for Continuous Three-dimensional Toolpath Strategy Using Wire Arc Additive Manufacturing for Free-form Thin Parts. (October 2022) - Giordano, A.; Diourté, A.; Bordreuil, C.; Bugarin, F.; Segonds, S.
Abstract: Wire Arc Additive Manufacturing (WAAM) is revolutionizing the field of Additive Manufacturing (AM) by being the technological solution to manufacture thin-walled structures of large dimensions and medium geometric complexity at reduced cost with an excellent buy-to-fly ratio. Manufacturing parts with this technology is nowadays done through 2.5D strategies. This type of strategy consists in cutting a 3D model using planar layers parallel to each other. This 2.5D technique limits the complexity of the geometries that can be produced in WAAM without taking advantage of height deposit modulation. It also requires several start/stop phases of the arc during the transition from one layer to another, which leads to poor quality. This paper presents a new fast and efficient path planning strategy aiming at creating a continuous manufacturing path, thus increasing poor part quality. This strategy so called "Scalar Thermal Field for Continuous Toolpath" is generating a continuous spiral manufacturing toolpath for thin shaped parts. The modulation of deposition, by controlling the welding torch travel speed at constant wire feed rate, allows continuous deposition of material throughout the manufacturing process. The keypoint of the method is the use of a thermal scalar field associated with a 6-axis robotic arm kinematics which allows the manufacturing of closed parts after optimal closure point determination or direct manufacturing of opened parts with non-planar free edges. Validation of the presented method is performed by manufacturing three distinct parts : an opened, a closed part and a multi-branch part. The fabrication of these parts and their precise measurement have shown the reliability and the restitution capacity of our method which is clearly superior to 2.5D strategies nowadays commonly used in WAAM technology. Highlights: Presents a new and easy to compute continuous toolpath generation method. Describes a path planning strategy using 5-axis with modulation of the deposit. Uses thermal scalar field for the generation of continuous toolpaths. Reduces the arc start/stop phases by using a continuous toolpath strategy. Validates the method by manufacturing and measuring three different types of parts.